Copper-clad laminate and preparation method thereof
By adopting a stacked structure of single-sided composite copper foil and thin glass fiber cloth in 5G products, the problem of high dielectric constant and dielectric loss values in the prior art is solved, and the stability and uniformity of dielectric performance are achieved , suitable for high-speed and high-frequency circuits.
Patent Information
- Application Number
- CN202411133097.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
The existing 5G products have high dielectric constant and dielectric loss values, and their dielectric performance is unstable, making it difficult to meet the needs of high-speed and high-frequency characteristics.
A thin glass fiber cloth with the same number of warp and weft yarns as reinforcement materials was used to form a semi-cured sheet by impregnation of resin glue, and a copper-clad foil laminate was prepared by hot pressing to control the thickness of the resin layer and the proportion of the glass fiber cloth. , ensure the stability of the dielectric constant and dielectric loss value.
It realizes the reduction of dielectric constant and dielectric loss value, ensures the stability and uniformity of the board, and is suitable for 5G products of high-frequency and high-speed circuits.
Smart Images

Figure CN119239072A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of basic materials in the field of electronic information, and more specifically, relates to a high-speed and high-frequency copper-clad laminate used in 5G products and a preparation method thereof. Background Art
[0002] With the rapid development of modern communication technology, the fifth generation of mobile communication technology 5G will become more and more popular in people's daily life. 5G communication is a new generation of broadband mobile communication technology with the characteristics of high speed, low latency and large connection. With the development of technology, people have higher requirements for communication, such as increased information communication flow, miniaturization and convenience of communication equipment. In order to obtain more information, by increasing the communication frequency to increase the bandwidth, the printed circuit boards in electronic products are required to have high frequency and high speed characteristics. In addition to having a low dielectric constant and dielectric loss constant, the copper clad laminate used in 5G products must also have stable dielectric properties. This requires that in the structure of the plate, the rough surface "copper teeth" of the copper foil is small and uniform, and the glass fiber cloth and organic resin components must also be relatively stable, so that the mass percentage between the two is consistent, otherwise it will cause fluctuations in the dielectric constant. At the same time, higher requirements are also put forward for the thickness uniformity of the plate. Summary of the invention
[0003] The object of the present invention is to provide a copper-clad laminate for 5G products, which has low dielectric constant and dielectric loss value and stable dielectric properties, and a preparation method thereof.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A copper-clad laminate comprises: a single-sided composite copper foil, the single-sided composite copper foil comprising a single-layer copper foil and a carrier film covering the single-layer copper foil; at least one layer of prepreg laminated on the single-sided composite copper foil, the prepreg being formed by impregnating a thin glass fiber cloth with a resin adhesive, the thin glass fiber cloth having the same number of warp yarns and weft yarns; the resin adhesive comprising: bisphenol A type cyanate resin, bicyclic cyclic epoxy resin, bisphenol A epoxy resin, cage-shaped silsesquioxane and mesoporous silica filler.
[0006] The copper-clad laminate as described above, further, both sides of the stacked prepregs are provided with the single-sided composite copper foil; or, one side of the stacked prepregs is provided with the single-sided composite copper foil.
[0007] In the copper-clad laminate as described above, further, the carrier film is one of polybutylene terephthalate film, polyethylene naphthalate film, polyethylene terephthalate film or polyimide film.
[0008] The copper-clad laminate as described above, further, the prepreg has a thickness of 0.09 to 0.120 mm.
[0009] The copper-clad laminate as described above, further, the thickness of the resin layer of the prepreg is 0.05 mm to 0.1 mm; and / or the thickness of the thin glass fiber cloth is less than 0.13 mm.
[0010] The copper-clad laminate as described above, further, the thin glass fiber cloth is 1652 type glass fiber cloth or 1678 type glass fiber cloth or 3070 type glass fiber cloth or 6060 type glass fiber cloth or 106 type glass fiber cloth or 101 type glass fiber cloth.
[0011] The copper-clad laminate as described above, further, the resin adhesive comprises: 15-30 parts by mass of bisphenol A type cyanate resin, 15-30 parts by mass of bicyclic cyclic epoxy resin, 30-50 parts by mass of bisphenol A epoxy resin, 5-15 parts by mass of cage-shaped silsesquioxane, 5-15 parts by mass of mesoporous silica filler, and 0.1-2.0 parts by mass of catalyst.
[0012] The copper-clad laminate as described above, further, has a dielectric constant of less than 3.8 and a dielectric loss value of less than 0.0080.
[0013] The present invention also provides a method for preparing the aforementioned copper-clad laminate, comprising the following steps:
[0014] Prepare resin glue; dissolve bisphenol A type cyanate resin, bicyclic cyclic epoxy resin, bisphenol A epoxy resin and catalyst in a solvent, then add cage-shaped silsesquioxane and mesoporous silica filler, stir evenly, and prepare resin glue;
[0015] The glass fiber cloth is immersed in the resin glue solution and baked to obtain a semi-cured sheet;
[0016] At least one prepreg is compounded with a single-sided composite copper foil, and after hot pressing and curing, a copper-clad laminate is obtained.
[0017] The preparation method as described above, further, the temperature of hot pressing molding is 170-190° C., and the curing time is 90-120 min.
[0018] It can be seen from the above technical scheme that the present invention adopts a single-sided composite copper foil composed of a single-layer copper foil and a carrier film covered on the single-layer copper foil as a conductive layer, and uses a thin glass fiber cloth with the same number of warp yarns and weft yarns as a reinforcing material to make a prepreg as an insulating layer. The thickness of the resin layer in the prepreg is controlled at 0.05mm~0.1mm, which is thinner than the resin layer of the conventional prepreg. The low dielectric constant and low loss of the copper-clad laminate are achieved from the copper foil structure and the prepreg structure. The above process stacking structure ensures the stability of the ratio of the reinforcing material to the resin in the board and the uniformity of the board, and ensures that the thickness tolerance is narrowed within a certain range, so that the dielectric constant and dielectric loss value of the board are maintained in a stable state. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 This is a schematic diagram of the structure of a copper-clad laminate according to an embodiment of the present invention;
[0021] Figure 2 The present invention is a flowchart of a method for preparing a copper-clad laminate according to an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with the accompanying drawings. When describing the embodiments of the present invention in detail, for the convenience of explanation, the drawings representing the device structure will not be partially enlarged according to the general proportion, and the schematic diagram is only an example, which should not limit the scope of protection of the present invention. It should be noted that the drawings are simplified in form and use non-precise proportions, which are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention. At the same time, in the description of the present application, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated; the terms "positive", "negative", "bottom", "upper", "lower", etc. indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to the present invention.
[0023] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, it can also be the internal connection of two elements, it can be a wireless connection, or it can be a wired connection. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0024] Conventional FR-4.0 copper clad laminates mostly use traditional bisphenol A epoxy resin glue and 7628 glass fiber cloth as reinforcing materials to make prepregs, and then multiple prepregs are stacked and hot-pressed with copper foil to make copper clad laminates. The thickness of 7628 glass fiber cloth is about 0.17mm, and the thickness of the prepreg made is 0.18-0.22mm, in which the resin component accounts for 38-48%. When several prepregs are stacked according to different board thickness requirements, in order to achieve the desired board thickness and tolerance, it is necessary to adjust the ratio of the resin component and the glass fiber cloth component in the prepreg to be consistent, but because the number of warp and weft yarns of 7628 glass fiber cloth is different, the content ratio of resin and glass fiber cloth will fluctuate, so it cannot be guaranteed that the ratio of the resin component and the glass fiber cloth component at any point in the board is the same, which will cause the dielectric constant and dielectric loss value of the board to have a large consistency difference, and it is high, showing an unstable situation.
[0025] In order to solve the problem that the dielectric constant and dielectric loss value of copper-clad laminates are high and the dielectric performance is unstable, the present invention uses single-sided composite copper foil as the conductive layer of the laminate, uses thin electronic-grade glass fiber cloth as the reinforcing material, and uses a high-performance resin-modified epoxy resin system as the insulating layer. The thin glass fiber cloth with the same number of warp yarns and weft yarns is impregnated in a resin glue with a low dielectric constant and a low loss constant to form a prepreg, and then the prepreg and the single-sided composite copper foil are compounded and hot-pressed into a laminate.
[0026] The thickness of the electronic-grade glass fiber cloth used in the present invention is less than 0.13 mm. The semi-cured sheet made of thin glass fiber cloth has a resin content greater than 50%, thereby ensuring that the ratio of reinforcing material to resin in the plate is greater than 50%. Relative to the reinforcing material, the resin has the characteristics of low dielectric constant, low loss constant, etc., so the use of thin glass fiber cloth can ensure that the plate has the characteristics of low dielectric constant, low loss constant, etc. In addition, the electronic-grade glass fiber cloth with the same number of warp and weft yarns and thin thickness is selected to ensure the consistency of the ratio of reinforcing material to resin in the plate, thereby improving the stability and uniformity of the dielectric constant and low loss constant of the plate.
[0027] like Figure 1 As shown, the copper-clad laminate of this embodiment includes a single-sided composite copper foil and a plurality of stacked prepregs, and the specific stacking structure can be: single-sided composite copper foil 2+prepreg 1+single-sided composite copper foil 2, that is, a plurality of prepregs 1 are arranged between two layers of single-sided composite copper foil 2. The stacking structure can also be single-sided composite copper foil 2+prepreg 1, that is, a plurality of prepregs 1 are arranged on a single-sided composite copper foil 2.
[0028] The single-sided composite copper foil 1 of the present invention is composed of a single-layer copper foil and a single-layer carrier film covering the single-layer copper foil, that is, a composite material with a film on one side and a copper foil on the other side. Specifically, the carrier film of the present invention can be a polybutylene terephthalate film (PBT film), a polyethylene naphthalate film (PEN film), a polyethylene terephthalate film (PET film) or a polyimide film (PI film). An adhesive is coated on the matte surface of the single-sided composite copper foil.
[0029] The semi-cured sheet is formed by impregnating glass fiber cloth with resin glue. The glass fiber cloth used in the present invention is a glass fiber cloth with the same number of warp yarns and weft yarns. The same number of warp yarns and weft yarns is conducive to maintaining a stable proportion of resin components in the board structure, and the thickness of the board is relatively uniform. The thickness of a single semi-cured sheet of the present invention is 0.09-0.120mm, and the thickness of the resin layer (also called cream layer) on the surface of the semi-cured sheet is 0.05mm-0.1mm. The resin component content is high and the surface of the glass fiber cloth is fine and smooth, which is conducive to ensuring low dielectric constant and low dielectric loss. Specifically, the model of the glass fiber cloth selected by the present invention can be 1652, 1678, 3070, 6060, 106, 101.
[0030] The resin glue used for preparing the semi-cured sheet of the present invention adopts a high-performance resin with a low dielectric constant and a high-performance epoxy resin to form a high molecular polymer with a relatively symmetrical structure and low polarity, and is compounded with a cage-shaped silsesquioxane and a mesoporous silica filler. The cage-shaped silsesquioxane and the mesoporous silica filler are used to improve the dimensional stability of the plate, and the dielectric constant and dielectric loss of the plate are not affected.
[0031] Specifically, the resin glue contains: 15 to 30 parts (mass parts) of bisphenol A cyanate resin, 15 to 30 parts of bicyclic cyclic epoxy resin, 30 to 50 parts of bisphenol A epoxy resin, 5 to 15 parts of cage-shaped silsesquioxane, 5 to 15 parts of mesoporous silica filler, and 0.1 to 2.0 parts of catalyst. The above raw materials are dissolved in a solvent, mixed at room temperature, and stirred evenly to form a resin glue. In specific applications, 50 to 200 parts of dimethylformamide can be used as a solvent. The catalyst can be one or more of acylacetone cobalt, dibutyltin dilaurate, nonylphenol, manganese octanoate, and zinc octanoate.
[0032] According to different requirements for the thickness of the sheet, a corresponding number of prepregs 2 are stacked together, such as 5 sheets (layers) of prepregs for a 0.5 mm thick sheet, 10 sheets (layers) of prepregs for a 1.0 mm thick sheet, and 15 sheets (layers) of prepregs for a 1.5 mm thick sheet. After the prepregs are stacked, they are compounded with a single-sided composite copper foil coated with an adhesive on the surface, and hot-pressed at 170 to 190°C in a hot press, and cured for 90 to 120 minutes to form a copper-clad laminate for PCBs of 5G products.
[0033] The present invention is further described below by specific examples. Unless otherwise specified, the reagents, materials and instruments used in the following description are all conventional reagents, conventional materials and conventional instruments, which can be commercially obtained, and the reagents involved can also be synthesized by conventional synthesis methods.
[0034] Example 1
[0035] like Figure 2 As shown, the steps of the method for preparing the copper-clad laminate of this embodiment are as follows:
[0036] S1, preparing resin glue; in the process of preparing the resin glue, all raw materials are calculated by weight, 15 parts of bisphenol A cyanate resin, 15 parts of bicyclic cyclic epoxy resin, 45 parts of bisphenol A epoxy resin, and 0.3 parts of catalyst are dissolved in dimethylformamide solvent, and then 5 parts of cage-shaped silsesquioxane and 15 parts of mesoporous silica filler are added, and stirred evenly to obtain a resin glue;
[0037] S2, dipping the glass fiber cloth in the resin glue obtained in step S1, and baking to obtain a prepreg. The thickness of the resin layer on the surface of the prepreg in this embodiment is 0.05 mm to 0.07 mm, and the thickness of a single cured sheet obtained after curing is 0.095 to 0.100 mm. This embodiment uses 1678 type glass fiber cloth, which has a fine surface, so that the ratio of the reinforcing material to the resin in the plate can be relatively stable, thereby keeping the dielectric constant and dielectric loss value of the plate in a more stable state.
[0038] S3. Stack 15 prepregs together, and cover the upper and lower surfaces or one side of the stacked prepregs with a single-sided composite copper foil. In this embodiment, both sides are covered with a single-sided composite copper foil, and the thickness of the single-sided composite copper foil is 0.018 mm. After hot pressing, a copper-clad laminate with a thickness of 1.5 mm for high-frequency and high-speed circuits is obtained.
[0039] The dielectric constant (1 MHz) and dielectric loss constant (1 MHz) of the copper-clad laminate prepared in this embodiment were tested and were 3.75 and 0.0073, respectively.
[0040] Example 2
[0041] S1, preparing resin glue; in the process of preparing the resin glue, all raw materials are calculated by weight, 25 parts of bisphenol A cyanate resin, 20 parts of bicyclic cyclic epoxy resin, 35 parts of bisphenol A epoxy resin, and 0.6 parts of catalyst are dissolved in dimethylformamide solvent, and then 10 parts of cage-shaped silsesquioxane and 10 parts of mesoporous silica filler are added, and stirred evenly to obtain a resin glue;
[0042] S2, immersing 1678 type glass fiber cloth in resin glue, and baking to obtain a prepreg. The thickness of the resin layer on the surface of the prepreg in this embodiment is 0.08mm-0.1mm, and the thickness of a single prepreg obtained after curing is 0.095-0.10mm;
[0043] S3. Ten prepregs are stacked together, and a single-sided composite copper foil with a thickness of 0.035 mm is covered on both sides. After hot pressing, a copper-clad laminate with a thickness of 1.0 mm for high-frequency and high-speed circuits is obtained.
[0044] The dielectric constant (1 MHz) and dielectric loss constant (1 MHz) of the copper-clad laminate prepared in this embodiment were tested and were 3.67 and 0.0065, respectively.
[0045] Example 3
[0046] S1, preparing resin glue; in the process of preparing the resin glue, all raw materials are calculated by weight, 30 parts of bisphenol A cyanate resin, 25 parts of bicyclic cyclic epoxy resin, 30 parts of bisphenol A epoxy resin, and 0.9 parts of catalyst are dissolved in dimethylformamide solvent, and then 15 parts of cage-shaped silsesquioxane and 5 parts of mesoporous silica filler are added, and stirred evenly to obtain a resin glue;
[0047] S2, immersing 3070 type glass fiber cloth in resin glue, and baking to obtain a prepreg. The thickness of the resin layer on the surface of the prepreg in this embodiment is 0.08mm-0.1mm, and the thickness of a single cured sheet obtained after curing is 0.095-0.120mm;
[0048] S3. Stack 1 semi-cured sheet together, cover both sides with a single-sided composite copper foil with a thickness of 0.015 mm, and perform hot pressing to obtain an ultra-thin copper-clad laminate with a thickness of 0.13 mm for high-frequency and high-speed circuits.
[0049] The dielectric constant (1 MHz) and dielectric loss constant (1 MHz) of the copper-clad laminate prepared in this embodiment were tested and were 3.62 and 0.0057, respectively.
[0050] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A copper-clad laminate, characterized in that: include: A single-sided composite copper foil, the single-sided composite copper foil comprising a single-layer copper foil and a carrier film covering the single-layer copper foil; At least one layer of prepreg laminated on the single-sided composite copper foil, wherein the prepreg is formed by impregnating a thin glass fiber cloth with a resin adhesive, and the number of warp yarns and weft yarns of the thin glass fiber cloth is the same; The resin glue contains: bisphenol A type cyanate resin, bicyclic cyclic epoxy resin, bisphenol A epoxy resin, cage-shaped silsesquioxane and mesoporous silica filler.
2. The copper-clad laminate according to claim 1, characterized in that: The single-sided composite copper foil is provided on both sides of the stacked prepregs; Alternatively, the single-sided composite copper foil is disposed on one side of the stacked prepregs.
3. The copper-clad laminate according to claim 1, characterized in that: The carrier film is one of a polybutylene terephthalate film, a polyethylene naphthalate film, a polyethylene terephthalate film or a polyimide film.
4. The copper-clad laminate according to claim 1, characterized in that: The thickness of the prepreg is 0.09-0.120 mm.
5. The copper-clad laminate according to claim 1, characterized in that: The thickness of the resin layer of the prepreg is 0.05 mm to 0.1 mm; And / or, the thickness of the thin glass fiber cloth is less than 0.13 mm.
6. The copper-clad laminate according to claim 1, characterized in that: The thin glass fiber cloth is 1652 type glass fiber cloth, 1678 type glass fiber cloth, 3070 type glass fiber cloth, 6060 type glass fiber cloth, 106 type glass fiber cloth or 101 type glass fiber cloth.
7. The copper-clad laminate according to claim 1, characterized in that: The resin glue contains: 15-30 parts by weight of bisphenol A cyanate resin, 15-30 parts by weight of bicyclic cyclic epoxy resin, 30-50 parts by weight of bisphenol A epoxy resin, 5-15 parts by weight of cage-shaped silsesquioxane, 5-15 parts by weight of mesoporous silica filler, and 0.1-2.0 parts by weight of catalyst.
8. The copper-clad laminate according to claim 1, characterized in that: The dielectric constant of the copper-clad laminate is less than 3.8, and the dielectric loss value is less than 0.0080.
9. The method for preparing a copper-clad laminate according to any one of claims 1 to 7, characterized in that: The following steps are involved: Prepare resin glue; dissolve bisphenol A type cyanate resin, bicyclic cyclic epoxy resin, bisphenol A epoxy resin and catalyst in a solvent, then add cage-shaped silsesquioxane and mesoporous silica filler, stir evenly, and prepare resin glue; The glass fiber cloth is immersed in the resin glue solution and baked to obtain a semi-cured sheet; At least one prepreg is compounded with a single-sided composite copper foil, and after hot pressing and curing, a copper-clad laminate is obtained.
10. The preparation method according to claim 9, characterized in that: The temperature of hot pressing molding is 170-190°C, and the curing time is 90-120 minutes.
Citation Information
Patent Citations
Cyanate resin composition and copper-clad plate manufactured by using same
CN102127296A
Halogen-free low-dielectric constant high-toughness copper foil-coated laminated board
CN102873940A
High-toughness copper-clad plate and preparation method thereof
CN107696646A
High-frequency resin prepolymer and high-frequency resin combination, prepreg, laminated board and interlayer insulating membrane prepared with same
CN109735086A
High-speed circuit copper-clad plate
CN208962615U
Cited By
Printed circuit board and assembling device thereof
CN119922823A
Printed Circuit Board and Its Assembly Device
CN119922823B